Theological Egoism In The Hadith of Dzul Khuwaishirah: A Critique of the Practice of Totalization In The Kharijite Doctrine A Levinasian Critique - Basyir, Muhammad Al; Muhid, Muhid (LP2M IAIN kUDUS, 2026)
This study examines theological egoism in the hadith of Dzul Khuwaishirah and its development in the takfiri doctrine of the Khawarij through the ethical perspective of Emmanuel Levinas. This study aims to analyze this form of theological egoism and formulate its implications for religious moderation. This study employs a literature review (library research) method with a philosophical and ethical interpretive approach based on the thought of Emmanuel Levinas as its analytical framework. Primary data include the hadith of Dzul Khuwaishirah in Sahih al-Bukhari and Sahih Muslim, as well as Emmanuel Levinas’s works, Totality and Infinity: An Essay on Exteriority and Otherwise than Being or Beyond Essence. The hadith corpus is analyzed through historical contextualization and the identification of the theme of theological egoism. At the same time, Levinas’s texts are used to examine the concepts of totalization, alterity, and asymmetrical responsibility as a framework for a critical reading of the hadith. The results of the study indicate that Dzul Khuwaishirah’s stance can be understood as a form of egology that absolutizes subjective judgment and disregards alterity. This pattern has developed within the Khawarij’s takfiri doctrine. This study demonstrates that religious moderation can be strengthened through an ethical orientation that places responsibility toward the other as the foundation for respect for human dignity.